1993
DOI: 10.1139/z93-002
|View full text |Cite
|
Sign up to set email alerts
|

Storage and translocation of integumentary calcium during the moult cycle of the terrestrial isopod Oniscus asellus (L.)

Abstract: The calcium content of pieces of integument of standardized size from various regions of the body was measured at all 15 stages of the intermoult cycle. Calcium resorbed from the posterior integument during premoult is stored mainly in the sternal calcium deposits of the anterior region, which contain 20% of total body calcium in late premoult. Earlier arguments that the deposits are not a store of calcium are refuted. These deposits are similar to gastroliths in both structure and function. After posterior ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 13 publications
0
40
0
Order By: Relevance
“…A study on the hemolymph calcium concentration of P. scaber revealed that calcium remains elevated after the anterior moult, suggesting another source for calcium ions (Ziegler and Scholz, 1997). P. scaber ingests the exuviae after each half moult, suggesting that the intestinal epithelium resorbs mineral from the exuviae that still contains considerable amounts of calcium carbonate (Steel, 1993). It is of interest that in the mineralizing cuticle many pore canals can be seen that are devoid of mineral.…”
Section: Resorption and Storage Of Accmentioning
confidence: 99%
See 2 more Smart Citations
“…A study on the hemolymph calcium concentration of P. scaber revealed that calcium remains elevated after the anterior moult, suggesting another source for calcium ions (Ziegler and Scholz, 1997). P. scaber ingests the exuviae after each half moult, suggesting that the intestinal epithelium resorbs mineral from the exuviae that still contains considerable amounts of calcium carbonate (Steel, 1993). It is of interest that in the mineralizing cuticle many pore canals can be seen that are devoid of mineral.…”
Section: Resorption and Storage Of Accmentioning
confidence: 99%
“…This biphasic moult allows the animals to reduce the loss of CaCO 3 by shifting it between the anterior and poster integument. This mode is generally utilized in terrestrial isopod species (Oniscidea) that developed large CaCO 3 -deposits within the ecdysial space between the new and old cuticle of the first four anterior sternites (Messner, 1965;Steel, 1993;Strus and Compere, 1996;Ziegler and Miller, 1997;. Deposition and resorption of the deposits is well studied in the common woodlouse Porcellio scaber (Ziegler, 1996(Ziegler, , 1997Hagedorn and Ziegler, 2002;Ziegler et al, 2002Ziegler et al, , 2004Fabritius and Ziegler, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like all Crustacea, in a process called moulting, isopods regularly shed the old cuticle and produce a larger one in order to grow. During the moulting cycle terrestrial isopods resorb ACC from the cuticle and store and recycle it to mineralise the new cuticle Numanoi, 1934;Steel, 1993;Ziegler, 1997;. Since ACC is about 10 times more soluble than crystalline calcium carbonate phases (Brečević and Nielsen, 1989), high relative amounts of ACC within proximal layers make perfect sense, when large amounts of calcium carbonate need to be stored and recycled in order to quickly restore the protective function of a thick cuticle (Hild et al, 2008).…”
Section: Distribution Of Calcite and Amorphous Calcium Carbonate In Tmentioning
confidence: 99%
“…Isopods molt by shedding first the posterior and then the anterior half of their mineralised cuticle and replace it by a new larger one to allow for growth. About 1 week before the molt, terrestrial species resorb Ca 2+ and HCO3 -from the posterior cuticle and store it between the old cuticle of the first four anterior sternites and the anterior sternal epithelium (ASE) as large CaCO3 deposits (Messner, 1965;Steel, 1993). For this to occur, Ca 2+ and HCO3 -are transported from the hemolymph across the ASE to form the deposits.…”
mentioning
confidence: 99%